2004
DOI: 10.1212/01.wnl.0000145975.58478.6d
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of numerical distances in the left side of space

Abstract: Normal subjects presented with a middle number and two left- and right-sided outer numbers overestimate the numerical distance between the middle number and that positioned at its left side. Repetitive transcranial magnetic stimulation (rTMS) of the right posterior parietal cortex specifically counteracts this bias, suggesting that the mental representation of space defined by numbers is shifted toward the left side depending on a greater activity of the right hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 21 publications
1
33
3
Order By: Relevance
“…For example, Göbel et al (2006) found a stronger behavioral effect with TMS over right PPC than with over left PPC. Accordingly, a significant effect for rTMS over the right but not over the left PPC was found in number bisection (Oliveri et al, 2004). Some other studies found selective effect for left PPC TMS in comparing numerical magnitues (e.g., Göbel et al, 2001;Rusconi et al, 2005), and Rusconi et al (2007) have recently observed that rTMS over both left and right PPC disrupted attentional orienting in number space.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, Göbel et al (2006) found a stronger behavioral effect with TMS over right PPC than with over left PPC. Accordingly, a significant effect for rTMS over the right but not over the left PPC was found in number bisection (Oliveri et al, 2004). Some other studies found selective effect for left PPC TMS in comparing numerical magnitues (e.g., Göbel et al, 2001;Rusconi et al, 2005), and Rusconi et al (2007) have recently observed that rTMS over both left and right PPC disrupted attentional orienting in number space.…”
Section: Discussionmentioning
confidence: 85%
“…Importantly, TMS applied over the right PPC also causes neglect-like symptoms in number bisection (Göbel et al, 2006). Also, TMS applied over the right PPC has been shown to correct leftward biases in number bisection (Oliveri et al, 2004). There is therefore evidence from both neglect patients as well as from normal subjects that the brain regions mediating the mental number line are similar to those involved in the representation of visual space and spatial allocation of attention.…”
Section: Introductionmentioning
confidence: 99%
“…This advantage is proposed to be equivalent to the one enjoyed by left-sided items in a horizontal arrangement of visually or haptically presented stimuli [Bradshaw, Nathan, Nettleton, Wilson, & Pierson (1987): rod centering] and referred to, alternatively, as "initial exploration asymmetry" (Ebersbach et al, 1996;Hättig, 1992), "left-side underestimation" (Bradshaw, Nettleton, Nathan, & Wilson, 1983), "right hemispatial inattention" (Weintraub & Mesulam, 1988) or "pseudoneglect" (Bowers & Heilman, 1980). Pseudoneglect along the mental number line was originally demonstrated in the bisection of numerical intervals (Oliveri et al, 2004). Its magnitude is sometimes influenced by the same factors that also determine the magnitude of attentional asymmetries in physical space (Longo & Lourenco, 2007), but Doricchi et al did not find a relationship between visual and number line bisection (Doricchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the concept of "pseudoneglect in number space" (Göbel, Calabria, Farne, & Rossetti, 2006;Oliveri et al, 2004) explains the SNB via spatial-attentional processes. Thus, SNB could be a consequence of a cerebral hemispheric imbalance in favour of righthemisphere spatial-attentional functions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that performance for physical line and mental number line bisection can correlate within individuals (Longo & Lourenco, 2007). Further, evidence from TMS has supported that similar brain areas are activated in both tasks (Cattaneo, Silvanto, Pascual-Leone, & Battelli.,, 2009;Gobel, Calabria, Farne, & Rossetti, 2006;Oliveri, Rausei, Koch, Torriero, Turriziani, & Caltigrone, 2004).…”
Section: Introductionmentioning
confidence: 99%